PERBANDINGAN TERAPI OMEPRAZOLE DAN RANITIDINE TERHADAP LAMA RAWAT INAP PASIEN DISPEPSIA DEWASA DI RSUD DR. DRADJAT PRAWIRANEGARA SERANG - Ayi Nabilah (2023)
Objective : Dyspepsia is a disorder of the digestive tract that is common and has been complained of by various groups of people. The National Consensus on the Management of Dyspepsia and Helicobacter pylori Infection recommends the initial management of dyspepsia, one of which is gastric acid antisecretory drugs. The most frequently used gastric acid antisecretory drugs in inpatient dyspepsia patients are omeprazole and ranitidine. Different drug mechanisms lead to different drug effectiveness which affects the patient's length of stay. This study aims to compare omeprazole and ranitidine therapy to the length of stay of adult dyspepsia patients at dr. Dradjat Prawiranegara Serang. Method : This is a analytical observational study with a cross-sectional approach to dyspepsia patients at RSUD dr. Dradjat Prawiranegara Serang. The sampling technique used was total sampling method and data analysis used Mann Whitney test. Result : The study was conducted on 64 patients and the results showed that the average length of stay in dyspepsia patients with omeprazole therapy was 1.91 (±0.893) days. In contrast, the average length of stay of dyspepsia patients with ranitidine therapy was 2.16 (±1.194) days. The results of the bivariate analysis comparing the length of stay in the two groups showed no significant differences with a value of p=0.542. Conclusion : The results of this analysis revealed that there was no discernible difference in the length of stay of dyspepsia patients whom treated with omeprazole and ranitidine at dr. Dradjat Prawiranegara Serang General Hospital.